After the Grab? Land Control and Regime Survival in Cambodia since 2012. Issue 3 (27th May 2021) - Loughlin, Neil; Milne, Sarah
ABSTRACT: The global land grab has played out vividly in Cambodia, giving rise to rural upheaval and new political dynamics. This article explores how the Cambodian government has dealt with the social and political consequences of this land grabbing, with the aim of exploring state formation in the context of socio-environmental disruption and dispossession. When a moratorium was declared in 2012, the ruling Cambodian People's Party faced one of its strongest political challenges, fuelled in part by land and resource conflicts. In this article, the focus is on the responses to this challenge, noting the recursive relationship between land administration and state formation. The analysis shows three tactics of land control used by the regime to ensure its survival after the grab: reform, repression and re-territorialisation. These tactics operate in parallel and sometimes contradictory ways, being highly performative in nature. We reveal a regime that uses political theatre to construct legitimacy and authority on the one hand, while deploying coercion and violence on the other. These observations complement typical diagnoses of Cambodia's politics as neo-patrimonial, highlighting the performative and symbolic nature of government actions, particularly in the land sector.